PENGALAMAN PSIKOSOSIAL PASIEN KANKER PAYUDARA YANG MENJALANI TERAPI KEMOTERAPI DI BLUD dr. ZAINOEL ABIDIN BANDA ACEH - Sitio, Roma (Jurnal Keperawatan Priority, 2019)
Breast cancer is a malignant neoplasmic disease originating from parenchyma. The physical and psychological changes experienced by cancer patients undergoing chemotherapy will contribute to the patient's social life such as changes in work status, changes in relations in society or changes in roles as wife and mother. Psychological problems experienced by advanced cancer patients stem from the decline in physical conditions due to illness and the side effects of therapy that are being undertaken. Psychological pressure in cancer patients undergoing treatment especially chemotherapy needs to be determined and understood. The purpose of this study was to explore the psychosocial experience of breast cancer patients undergoing chemotherapy. The research was a descriptive phenomenology design with as many as 10 participants and data collection through in-depth interviews conducted at the BLUD dr. Zainoel Abidin Hospital Banda Aceh in the Thursina 2. This study found 4 themes: psychological response after therapy, social support, hopes after undergoing therapy, and perceptions of health care providers. Based on the results of this study, the researchers suggested that health service providers, especially nurses, be expected to provide support from both emotional support and information support to increase women's enthusiasm and hope after undergoing chemotherapy.